H PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWANPADA UD. YAMAHA ISTANA SEPEDA BALANGAN - Haris Irawan Iswadi (Jurnal Ilmu Ekonomi dan Bisnis, 2019)
The study aims to determine the effect of education and training on employee performance in the service division UD. Yamaha Bike Palace Balangan. The sampling method done by directly selecting 36 employees. Data collection methods used direct interviews with parties involved with the problem being discussed and provide questionnaires to employees in accordance with the research conducted. Data were analyzed using qualitative and quantitative methods simple regression analysis formulas, T-Tests, and Determination Coefficient Test (R2) with helped by SPPS 18 software. Based on the analysis results, the regression equation: Y = 5.221 + 0.946X. The results of this study: T-test variables of education and training are known have a significant positive effect on employee performance, because the significance level is 5% greater than t-table (13,443> 2,032). The determination coefficient (R2) is 0.842, which means the ability education and training variable (X) can affect the employee performance variable (Y) by 84.2%.